Investor behavior on extreme situations of speculation and crash: an approach based on iterated prisoners dilemma - Silva, R. (2017)
In this paper, the development of an analysis based on the investor behavior on situations of speculation and crash on stock markets is made. An approach to the investor main behavioral features, especially the ones related to the cognitive and decision-making matters, in order to obtain an individual and an aggregated behavioral profile of the investor on situations of extreme events.